2022
DOI: 10.3390/nano12152728
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Labeled Iron Oxide Nanoparticles as Dual-Modality Contrast Agent: A Preliminary Study from Synthesis to Magnetic Resonance and Gamma-Camera Imaging in Mice Models

Abstract: The combination of two imaging modalities in a single agent has received increasing attention during the last few years, since its synergistic action guarantees both accurate and timely diagnosis. For this reason, dual-modality contrast agents (DMCAs), such as radiolabeled iron oxide (namely Fe3O4) nanoparticles, constitute a powerful tool in diagnostic applications. In this respect, here we focus on the synthesis of a potential single photon emission computed tomography/magnetic resonance imaging (SPECT/MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…All reagents and solvents used for radiolabeling of DPD-Fe 3 O 4 with 99m Tc and the appropriate equipment employed to determine its radiolabeling yield are described in detail in the respective section of our previous study, which can be found in [36].…”
Section: Methodsmentioning
confidence: 99%
“…All reagents and solvents used for radiolabeling of DPD-Fe 3 O 4 with 99m Tc and the appropriate equipment employed to determine its radiolabeling yield are described in detail in the respective section of our previous study, which can be found in [36].…”
Section: Methodsmentioning
confidence: 99%
“…Karageorgou et al [ 40 ] have focused on the synthesis and subsequent in vitro and in vivo evaluation of RIONs for dual imaging with SPECT and MRI. The RIONs consist of 99m Tc radiolabeled and 2,3-dicarboxypropane-1,1-diphosphonic acid coated IONs ( Figure 4 a).…”
Section: Passive Spect/mri Dmcamentioning
confidence: 99%
“…For both media (PBS and human serum), the stability results are determined by thin layer chromatographic analysis, using acetone and citrate solution (0.1 M) as the mobile phases. In the case of the stability of RIONs in human serum, the acetone-developed chromatograms show no release of free 99m Tc from the RIONs incubated in human serum for up to 24 h [ 40 ]. According to the authors, the slight decrease observed (67.3%) is expected due to the presence of serum proteins that may bind 99m Tc, ultimately affecting the original DMCA [ 40 ].…”
Section: Passive Spect/mri Dmcamentioning
confidence: 99%
See 2 more Smart Citations